Hubungan Durasi Hemodialisa dengan Tekanan Darah Pasien Gagal Ginjal Kronis: Hemodialysis Duration and Its Relationship with Blood Pressure in Patients with Chronic Renal Failure - Sri Suliah; Feri Catur Yuliani; Yeni Rusyani (Jurnal Keperawatan Berbudaya Sehat, 2026)
Hemodialysis is renal replacement therapy which is important for the patient of chronic renal failure. Hemodialysis procedures are currently experiencing rapid development, it’s often stated that many patients experience medical problems during hemodialysis. Common complications during hemodialysis include hemodynamic disturbances. The  goal of this research is to determine if there is a correlation between the lenght of hemodialysis sessions and blood pressure levels in chronic renal failure patients in the hemodialysis ward of an Pati Islamic Hospital. This research was a cross-sectional approach which is monitoring and measuring the patient’s blood pressure before and after the hemodialysis session.  The statiscal test used spearman rank In this research, it was found that the matority of hemodialysis sessions were short in duration whic is 37 (77,09%) respondents. While blood pressure is hypertension, which is 36(75%) respondents. As indicated by Spearman’s rank correlation, the obtained value is p value 0,406 with a = 0,05. If p value >a, it can be concluded that there is no correlation between hemodialysis duration and the blood pressure of patients with chronic renal failure.The research showed that there was no relationship between the duration of hemodialysis and the blood pressure of patients with chronic renal failure.